Analysis Of Diet, Risk Factors, Treatment Profile and Complications of Diabetes in Surat City - Choksi, Vivek K; Dave, Kairavee D; Panchal, Shaishav J (National Journal of Community Medicine, 2011)
This study was conducted among 69 known diabetes patients regarding diet, habits, risk factors, complications and treatment. We found that all the respondents were aware of the complications related to Diabetes. The diagnosis made by routine checkup was in 66.6% and by presenting complaints only 26% which showed that as diabetes is asymptomatic, its diagnosis is made late and patients are more prone to complications.